2007
DOI: 10.1007/s10529-006-9269-2
|View full text |Cite
|
Sign up to set email alerts
|

Production, formulation and antagonistic activity of the biocontrol like-yeast Aureobasidium pullulans against Penicillium expansum

Abstract: Aureobasidium pullulans (de Bary) Arnaud (Ach 1-1) was grown in a glucose fed-batch fermentor to 106 g dry wt l -1 in 48 h. The cells were dried in a fluidized bed dryer with a final viability of 62%. After 7 months at 4°C, the viability was 28% of the initial value (= 2.3 · 10 10 c.f.u. g -1 dry matter). A protection level of 89% was achieved with the biomass preparation at 1 · 10 8 c.f.u. ml -1 after 28 and 7 days for apples stored respectively at 5 and 25°C against Penicillium expansum. Our process is suita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 10 publications
1
26
0
Order By: Relevance
“…Among these amino acids, glycine, glutamic acid and especially serine appear to be the most limited nutrients in this mechanism. In a recent study (Mounir et al, 2007), it was found that strain Ach 1-1 was very effective in controlling blue mould on apples at both 5 • C and 25 • C and that biomass production in a fermentor (fed-batch) as well as drying (fluidized bed) did not affect its antagonistic activity. As new potential biocontrol agents, the specific identification of strains Ach 1-1 and 1113-5 using monitoring tools is needed for their practical application and for their commercial use.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Among these amino acids, glycine, glutamic acid and especially serine appear to be the most limited nutrients in this mechanism. In a recent study (Mounir et al, 2007), it was found that strain Ach 1-1 was very effective in controlling blue mould on apples at both 5 • C and 25 • C and that biomass production in a fermentor (fed-batch) as well as drying (fluidized bed) did not affect its antagonistic activity. As new potential biocontrol agents, the specific identification of strains Ach 1-1 and 1113-5 using monitoring tools is needed for their practical application and for their commercial use.…”
Section: Discussionmentioning
confidence: 98%
“…doi: 10.1016/j.postharvbio.2008.05.011 In this context, A. pullulans strains Ach 1-1 and 1113-5 were isolated from 'Golden Delicious' apples for their high antagonistic activity (more than 80%) against B. cinerea and P. expansum, two major postharvest pathogens of apples (Achbani et al, 2005). With regard to strain Ach 1-1, a process suitable for producing large quantities has been developed (Mounir et al, 2007) and competition for apple nutrients, most particularly amino acids, may be the main mechanism of its biocontrol activity against blue mold caused by P. expansum on harvested apple fruit (Krimi Bencheqroun et al, 2007). The practical application of Ach 1-1 and 1113-5 strains as biocontrol agents will require the development of monitoring methods allowing their specific identification and their quantification.…”
Section: Introductionmentioning
confidence: 99%
“…In general, liquid-phase cultures are used for bacteria and yeasts and solid-phase cultures are used for most fungi. Optimized mass production systems have been described for some postharvest biocontrol agents, including bacteria such as P. agglomerans CPA-2 (Costa et al, 2001), P. agglomerans PBC-1 (Manso et al, 2010) and B. subtilis CPA-8 (Yánez-Mendizábal et al, 2012b), yeasts such as C. sake CPA-1 (Abadias et al, 2003a,b), A. pullulans (Mounir et al, 2007), and Rhodotorula minuta (Patiño-Vera et al, 2005), and fungi such as Penicillium frequentans 909 (De Cal et al, 2002), and Epicoccum nigrum (Larena et al, 2004).…”
Section: Mass Production and Fermentationmentioning
confidence: 99%
“…Fluidized bed-drying is a costeffective method of drying that can be used to dry heat-sensitive microorganisms because the drying temperatures are relatively low. Fungi such as E. nigrum (Larena et al, 2003) and P. frequentans (Guijarro et al, 2006), the yeast-like fungus, A. pullulans (Mounir et al, 2007), and the yeast, C. sake CPA-2 (Usall et al, 2009) have all been successfully dried using fluidized bed-drying. In contrast, liquid formulations are the simplest way to stabilize the viability of microbial cells.…”
Section: Formulationmentioning
confidence: 99%
“…Vuill and Aspergillus niger Tiegh on table grapes (Castoria et al 2001), and the ochratoxigenic Aspergillus carbonarius (Bainier) Thom. on table grapes and strawberry (Lima et al 1997;Castoria et al 2001;De Felice et al 2008;De Curtis et al 2012b), against B. cinerea and P. expansum on apples (Castoria et al 2001;Ippolito et al 2000;Mounir et al 2007), against three species of the genus Monilinia on stone fruit (Mari et al 2012). De Felice et al (2008) observed for the first time that three strains of A. pullulans were the effective biocontrol agents in reducing both severity of Aspergillus rots in the vineyard and ochratoxin A (OTA) accumulation in wine grapes.…”
Section: Introductionmentioning
confidence: 99%